Phenolic Compounds and Carotenoids from the Leaves of Gymnosporia chevalieri Tard. - Doan, Thi Ai Nghia; Hoang, Thi Nhu Hanh; Le, Tuan Anh; Le, Thi Hong Van; Ho, Viet Duc (Tạp chí Y Dược Huế, 2025)
Background: The Gymnosporia genus holds substantial potential for bioactive compound discovery, yet its phytochemical composition remains underexplored relative to its botanical diversity. In Vietnam, aside from preliminary studies on G. stylosa, systematic research on Gymnosporia species is notably lacking. This study provides the understanding of the chemical constituents of G. chevalieri, establishing a basis for future research on its potential applications and bioactive properties. Materials and methods: The leaves of G. chevalieri were macerated in methanol to produce a crude extract, which was further fractionated via liquid-liquid partitioning using n-hexane and ethyl acetate as solvents. Compounds were then isolated and purified using various chromatographic techniques. Structural elucidation was achieved through 1D- and 2D-NMR and HR-ESI-MS analysis, supported by comparison with previously reported spectroscopic data. Results & Conclusion: Seven phenolic compounds and two carotenoids were isolated from G. chevalieri leaves. These were identified as syringaldehyde (1), 3,7-dihydroxy-6-methoxy-2,7-dimethyldibenzofuran (3), atalantoflavone (4), lutein (6), lutein 3′-methyl ether (7), and two mixtures: 4-hydroxybenzaldehyde (2a) with 4-hydroxy-3-methoxybenzaldehyde (2b), and breynioside B (5a) with 6′-O-vanilloylarbutin (5b). Notably, compounds 2-7 were isolated from the Gymnosporia genus for the first time.